Development of the epidemiology and outcomes of out-of-hospital cardiac arrest using data from the German Resuscitation Register over a 15-year period (EpiCPR study). (January 2023) - Hubar, Iryna; Fischer, Matthias; Monaco, Tobias; Gräsner, Jan-Thorsten; Westenfeld, Ralf; Bernhard, Michael
Abstract: Background: Sudden cardiac arrest is a relevant problem with a significant number of deaths in Europe. Aim: Using data from the German Resuscitation Register (GRR), we examined changes in epidemiology and therapeutic interventions over a 15-year period in order to identify key factors contributing to favourable outcome in out-of-hospital cardiac arrest (OHCA) patients. Methods: GRR data were analysed in 5-year periods (2006–2010 vs 2011–2015 vs 2016–2020) representing changes in the European Resuscitation Council (ERC) guidelines. Group comparison of OHCA patients was made for epidemiological and resuscitation-associated factors. Endpoints included 30-day survival and hospital discharge with a good neurological outcome (CPC 1, 2). Matched-pair analysis compared outcomes, and multivariate binary logistic regression analysis identified variables with effects on survival. Results: A total of 42, 997 GRR patients were studied (2006–2010: n = 3, 471, 2011–2015: n = 16, 122, 2016–2020: n = 23, 404). Proportion of patients over 80 years, use of intraosseous (IO) access and supraglottic airway devices, rate of bystander CPR, and the proportion of telephone CPR increased over the study period. The 30-day survival, and hospital discharge rates with CPC1/2 were unchanged. After adjusting cohorts using matched pairs, a higher CPC1, 2 rate was observed (8.8 vs 10.2%, p < 0.03). Logistic regression analysis showed that IO and SAD had an unfavourable impact on outcome. Conclusion: Despite a significant increase in bystander and telephone CPR rates, no improvement in 30-day survival and hospital discharge rate with CPC1, 2 was observed. Initial rhythm (VF/VT), cardiac and hypoxic cause of CA, bystander CPR and IV access were identified as factors associated with a favourable neurological outcome.